Two phase replication approach for MANETs. (27th July 2009) - Moussaoui, S.; Guerroumi, M.; Badache, N.
Data replication is a key approach for achieving high accessibility on mobile ad hoc networks. We propose a new replication approach based on two main phases. In the first phase, primary replicas for new shared data are created at k hops distance. This is a preventive means in case of unpredictable partitioning. In the second phase, these replicas are dynamically relocated. To preserve data availability, it considers user needs, node neighbourhood and the access response time. We propose three data replication methods based on this two phase approach. The simulation results indicate that the methods can increase the data accessibility.